Priority setting in an acute care hospital in Argentina: a qualitative case study - Gordon, Heather; Kapiriri, Lydia; Martin, Douglas K. (Acta Bioethica, 2009)
Purpose: To describe and evaluate priority setting in an Acute Care hospital in Argentina, using Accountability for Reasonableness, an ethical framework for fair priority setting.  Methods: Case Study involving key informant interviews and document review. Thirty respondents were identified using a snowball sampling strategy. A modified thematic approach was used in analyzing the data.  Results: Priorities are primarily determined at the Department of Health. The committee which is supposed to set priorities within the hospital was thought not to have much influence. Decisions were based on government policies and objectives, personal relationships, economic, political, historical and arbitrary reasons. Decisions at the DOH were publicized through internet; however, apart from the tenders and a general budget, details of hospital decisions were not publicized. CATA provided an accessible but ineffective forum for appeals. There were no clear mechanisms for appeals and leadership to ensure adherence to a fair process. Conclusions: In spite of their efforts to ensure fairness, Priority setting in the study hospital did not meet all the four conditions of a fair process. Policy discussions on improving legitimacy and fairness provided an opportunity for improving fairness in the hospital and Accountability for Reasonableness might be a useful framework for analysis and for identifying and improving strategies.